Microfluidics pushes forward microscopy analysis of actin dynamics - Jégou, Antoine (Landes Bioscience, 2011)
Actin filaments, an essential part of the cytoskeleton, drive various cell processes, during which they elongate, disassemble and form different architectures. Over the past 30 years, the study of actin dynamics has relied mainly on bulk solution measurements, which revealed the kinetics and thermodynamics of actin self-assembly at barbed and pointed ends, its control by ATP hydrolysis and its regulation by proteins binding either monomeric actin or filament ends and sides. These measurements provide quantitative information on the averaged behavior of a homogeneous population of filaments. They have been complemented by light microscopy observations of stabilized individual filaments, providing information inaccessible using averaging methods, such as mechanical properties or length distributions. In the past ten years, the improvement of light microscopy techniques has allowed biophysicists to monitor the dynamics of individual actin filaments, thus giving access to the length fluctuations of filaments or the mechanism of processive assembly by formins. Recently, in order to solve some of the problems linked to these observations, such as the need to immobilize filaments on a coverslip, we have used microfluidics as a tool to improve the observation, manipulation and analysis of individual actin filaments. This microfluidic method allowed us to rapidly switch filaments from polymerizing to depolymerizing conditions, and derive the molecular mechanism of ATP hydrolysis on a single filament from the kinetic analysis of its nucleotide-dependent disassembly rate. Here, we discuss how this work sets the basis for future experiments on actin dynamics, and briefly outline promising developments of this technique.